2015
DOI: 10.14740/jocmr2147w
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy in Treatment of Oral Lichen Planus

Abstract: Oral lichen planus (OLP) is a relatively common chronic immunologic mucocutaneous disorder. Although there are many presenting treatments, some of them proved its failure. Recently, the use of photodynamic therapy (PDT) has been expanding due to its numerous advantages, as it is safe, convenient, and non-invasive and has toxic effect towards selective tissues. This article provides comprehensive review on OLP, its etiology, clinical features and recent non-pharmacological treatments. We also describe the topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…On the other hand, PDT is safe, painless, noninvasive, inexpensive, and can be used without clinical contraindication. [18][19][20] In our literature review, 221 previous reported cases of LJSGH were found with no clear gender preponderance (Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] This number may be an overestimation or an underestimation, as the disease is recently described and the diagnostic criteria has not been well established in some reports.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, PDT is safe, painless, noninvasive, inexpensive, and can be used without clinical contraindication. [18][19][20] In our literature review, 221 previous reported cases of LJSGH were found with no clear gender preponderance (Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] This number may be an overestimation or an underestimation, as the disease is recently described and the diagnostic criteria has not been well established in some reports.…”
Section: Discussionmentioning
confidence: 79%
“…The primary goal is to reduce the pain associated with OLP lesions. At present, the following therapies have been evaluated for treating symptomatic OLP cases: Topical corticosteroids includes clobetasol, betamethasone, dexamethasone and triamcinolone; topical calcineurin inhibitors (TCIs) such as tacrolimus, pimecrolimus; retinoid such as tretinoin; photochemotherapy, photodynamic therapy[ 17 ] and traditional medicines (aloe vera gels and curcuminoids). In EBV-associated OLP lesions, treatment regimen should be modified by supplementing mainly with antioxidants and immunomodulatory drugs which could help overcome immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…PDT involves the administration of a photosensitizer or phototherapeutic agent to a diseased tissue of interest, followed by the photoactivation of that agent by a coherent laser light source or light-emitting diode at a specific wavelength [5]. When a photochemical cell reaction occurs, it is used to selectively destroy the target tissue [6] [7] [8]. Phthalocyanines (Pcs), porphyrin analogues, are the second generation of photosensitive substances that have been used in the treatment of skin diseases, such as basal cell carcinoma, psoriasis and actinic keratosis, and bacterial and viral manifestations, often showing positive results in reducing injury with minimal or no toxicity [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%